Kriteria reka bentuk persekitaran kampus yang kondusif bagi institusi pengajian tinggi di Malaysia - Suhana, Shamsudin; Lamit, Hasanuddin; Omar, Rozeyta; Md. Noor, Masliyana (Universiti Teknologi Malaysia, 2007)
This research aims to identify problems and issues relating to the planning and design of the universities' campus in Malaysia with emphasis given to the effectiveness of the campus in providing an environment that is conducive for learning. A case study approach was adopted to study the problems and the current situation of the institution of higher learning in Malaysia. This research is limited to the campus of public funded universities and that of the external environment outside buildings. Four universities in Malaysia were selected as the case studies based on their status and their age namely Universiti Malaya, Universiti Teknologi Malaysia, Universiti Islam Antarabangsa Malaysia and Universiti Malaysia Sabah. The research techniques adopted were questionnaire survey, focus interview, behavioural observation and visual survey. A bench marking exercise was also conducted with universities of the developed countries in the Asia region that share similar cultural and climatic conditions. These universities are University of Melbourne, University of Sydney, University of New South Wales, University of Queensland, University of Monash dan Australian National University, University of Tokyo, University of Osaka, University of Kyoto and Tokyo Institute of Technology. The data collected were analyzed using descriptive statistics with the aid of SPSSx package and qualitative analysis. The research discovered that there are several weaknesses regarding the planning, design, landscape and social life in the campus. A comparative analysis with the bench marking findings was done as a means to prepare a compendium consisting of planning and design guidelines for a more conducive environment, as a product of this research.